PENGARUH PENGETAHUAN INVESTASI DAN MOTIVASI INVESTASI TERHADAP MINAT BERINVESTASI PADA MAHASISWA UNIVERSITAS MAJALENGKA - Wulan Riyadi; Engkun Kurnadi (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The rapid development of technology and information has caused investment to experience changes to adapt to the conditions and circumstances that occur, the growing and advancing economy of a country is usually the investment alternatives offered are increasing and varied, which is one indicator in viewing and measuring the economy of a country in order to improve welfare people. This study aims to determine how the influence of investment and motivation on investment interest in Majalengka University students. This research is a type of quantitative research using a descriptive and verification approach. The population in this study were all students of Majalengka University with a total sample of 150 respondents. The sampling technique used was non-probability sampling with incidental sampling. The data collection technique in this study was a questionnaire using a Likert scale. Data analysis used multiple regression analysis, starting with the classical assumption test and the coefficient of determination and then testing the hypothesis. The results showed that investment knowledge, investment motivation and interest in investing were in the high category. The results of hypothesis testing indicate that investment knowledge and investment motivation have a positive and significant effect on investment interest, either partially or simultaneously.